Perancangan Sistem Manajemen Stok Buku Perpustakaan Berbasis Web Menggunakan Metode Agile - Sukrinah; Tetta Thirza Herdyawan (PT Jurnal Cendekia Indonesia, 2025)
School libraries are very important as a place to get information and references during the learning process. However, the manual management system that is still used causes a number of problems. Some of them are recording errors, delays in returning books, and limited access for teachers and students to information. This study develops a web-based book stock information system using the Agile method. This method was chosen because it is flexible and allows gradual development through sprint iterations, which makes it more responsive to changes in user needs. This system allows printing reports, borrowing and returning, book and category management, and multi-role login features. Testing shows that all features run as expected without significant errors. The implementation results show that the system can speed up book management, make data clearer, and allow everyone in the school to access information. It is hoped that this study will provide solutions to library digitization problems and also be a reference for the development of similar systems in other educational institutions.